THE INFLUENCE OF REINSURANCE RATE, LOAN INTEREST RATE AND BANK'S FEE BASED INCOME AGAINST THE PREMIUM RATE ON CREDIT LIFE INSURANCE (CASE STUDY: CREDIT LIFE INSURANCE’S POLICY HOLDER OF PT INDOSURYA LIFE IN 2018) - Markonah, Markonah (Dinasti Publisher, 2021)
This research has purposes to learn further about the impact of reinsurance rates, loan interest and fee-based income towards premium rates on credit life insurance. The unit of analysis was 50 credit life insurance policy holders at PT Indosurya Life throughout 2018. The independent variables that used in this research are reinsurance rates, loan interest and fee based income. While the dependent variable is premium rate on credit life insurance. The sample collected method was taken by saturated sampling. Researchers took the entire population as a sample where the number of samples used were 50 policy holders from credit life insurance which used premium rates and types of effective loan interest for 40 years of age with 5 years of insurance period. The analytical method used was multiple regression analysis and hypothesis test which is done by t-test. And according to the rdata analysis result, loan interest and fee-based income had a positive and significant affect towards credit life insurance's premium rates. Meanwhile, the reinsurance rate variable did not related to credit life insurance's premium rate. It is very recommended to PT Indosurya Life to increase the premium rate on its credit life insurance, so that will increase its Fee Based Income aswell.